STRATEGI ACADEMIC SELF-MANAGEMENT SISWA DALAM MENYELESAIKAN SEKOLAH SELAMA 2 (DUA) TAHUN DENGAN SISTEM KREDIT SEMESTER (SKS) (STUDI PADA SISWA KELAS XI SMA) - Reksiana; Ade Kamalia (Perspektif Ilmu Pendidikan, 2020)
This research is based on problems related to self-management of students who are less organized, less motivated, and problems of learning interest. The purpose of this study is to describe the actual state of the objects studied systematically, actual, accurate and in-depth related to facts about the academic self-management strategies of students in learning to complete studies for 2 (two) years in the semester credit system program (SKS) . The method used in this research was qualitative with descriptive analysis type. Data collection techniques used in the form of participatory observation, interviews and documentation. While the data analysis technique used the Miles and Huberman models. The results showed that self-talk is one of the most contributing aspects in providing motivation to students. Other aspects that also contribute to motivating students such as the selection of learning methods in accordance with learning styles, the use of time based on priorities, deadlines, complexity of tasks, physical and social environment and the ability of students to evaluate themselves for learning purposes.